Participants’ Satisfaction with the Indonesian National Police Recruitment Service Quality: Trust as a Mediator - Afif, Abdurrahman; Sah, Tomi (International Journal of Magistravitae Management, 2024)
The recruitment process of the Indonesian National Police is a vital mechanism for ensuring high-quality entrants into law enforcement in Indonesia. This study aims to identify the factors influencing participants’ satisfaction with the recruitment service quality, with a particular emphasis on trust as a mediating factor. A total of 246 recruitment participants completed a questionnaire designed to assess key service quality dimensions and their impact on trust and satisfaction. Structural Equation Modeling (SEM) using Partial Least Squares (PLS) was employed to analyze the relationships among service quality, trust, and satisfaction. The findings reveal that service quality has a direct, positive, and significant effect on participants’ trust. In turn, trust also directly, positively, and significantly impacts satisfaction. Furthermore, trust was found to mediate the relationship between service quality and satisfaction, highlighting its critical role in fostering a positive recruitment experience. This study provides valuable insights into the Indonesian National Police recruitment process and serves as a foundation for improving service quality and satisfaction levels in police recruitment services.